Porphyrin biosynthesis and enzymic studies in erythrocytes from normals and porphyric humans - Parera, V.E. (1980)
1. 1. Studies on porphyrin biosynthesis from exogenus ALA, at various time intervals as well as direct enzyme measurements (aminolevulimc acid dehydratase (ALA-D); porphobilinogenase (PBG ase) and deaminase were carried out in hemolysates of human erythrocytes from healthy controls and patients with lead poisoning (Pb), acute intermittent porphyria (AIP), porphyria cutanea tarda (PCT), erythropoietic protoporphyria (EPP), variegate porphyria (VP) and congenital erythropoietic porphyria (CEP). 2. 2. Inhibited ALA-D in Pb, reduced PBGase and deaminase in AIP, lower uroporphyrinogen decarboxylase in PCT, and diminished isomerase in CEP, were confirmed. In addition, ALA-D was found, reduced in AIP, unchanged in PCT and increased in EPP, VP and CEP. PBGase and deaminase were, on the other hand, increased in Pb and PCT, unchanged in VP and diminished in EPP and CEP. 3. 3. Total porphyrin biosynthesis is a function of time; compared to normals, is lower in CEP and AIP, but higher in PCT. 4. 4. The porphyrin profile changes along the time; uroporphyrin increases at longer intervals while that of coproporphyrin concomitantly diminished. A significance enhancement of octacarboxylic porphyrins was observed during the entire duration of the incubation in PCT hemolysates. In CEP the main porphyrin was always uroporphyrin I. 5. 5. Studies on both total porphyrins formed and their distribution were performed in hemolysates from cases of non-hereditary and hereditary PCT and AIP, before and after therapy. © 1980.